Software development for engineers with C, Pascal, C++, Assembly Language, Visual Basic, HTML, JavaScript, and Java - Buchanan, William
Specialisation in software has become a thing of the past. With the move towards graphical user interface programming, engineers must have a sound knowledge of several programming languages and for the first time most of the main technical languages are introduced in a single volume. All the example programs included relate to real life applications to provide a long needed reference that students will find invaluable throughout their studies, and a definitive guide for professional developers requiring an insight into other languages. Using C++ and Pascal to provide a basic grounding in software development the author then goes on to introduce more advanced concepts such as object-orientated design through the development of C++. Sections on Visual Basic and 80X86 Assembly Language follow before Java, Windows, NT and DOS are introduced, finishing with an overview of the UNIX system.